To join or not to join? The impact of social interactions on local participation decisions - Rixt Bijker; Eveline S. van Leeuwen; Paul Koster (Tinbergen Institute, 2019)
This paper investigates how social interactions impact the decision to participate in one's local environment. Existing work often reports correlations between social interactions and local participation, but it is unclear what the causal direction of this relationship is. A key contribution of this paper is that we are able to estimate the causal effect of social interactions on the decision to participate by systematically varying social attributes in a choice experiment. Based on a large-scale survey in one Dutch municipality we analyze 3894 choice observations of 435 respondents. Our sample includes respondents who currently participate and respondents who do not. We find that at the recruitment stage being asked by a friend or acquaintance significantly increases the chances to volunteer. We also find significant homophily effects in terms of age as well as for the characteristics of the group already participating. Financial incentives have significant negative impacts on the decision to participate.
Keywords: C90; Z13; L30; R58; 330; Social interactions; Discrete choice experiments; Homophily; Volunteering